Pengaruh Pelabelan dan Brаnd Image terhadap Minat Ulang Beli Pelanggan (Studi pаdа Mаhаsiswа STIA Bayuangga Probolinggo yаng Mеmbеli Kosmetik Viva) - Novi Sri Sandyawati (Departement of Mathematics Education, 2022)
This study aims to examine and explain the significant effect of pelebelans on the interest of re-buying Viva cosmetics products on STIA Bayuangga Probolinggo. The study uses explanatory research methods carried out through data collection in the field. the population of all Viva cosmetic product users in college students STIA Bayuangga Probolinggo with a sample of 98 female students, data analysis using statistical methods of Multiple Linear Regression and testing of hypotheses and coefficients is terminated. Based on the results of the study showed that Pelebelan can increase the interest of re-buying Viva cosmetics products in college students STIA Bayuangga Probolinggo and Brand Image can increase interest in repurchasing Viva cosmetics products to students STIA Bayuangga Probolinggo